Pesantren dan Reproduksi Kelas Menengah Indonesia: Studi atas Pesantren Wirausaha Kebon Cinta dan Pesantren Bina Insan Mulia - Majdudin Nurul Huda (CV. Kalimasada Group, 2025)
This study aims to examine three issues: (1) the contribution of pesantren and their graduates to the formation of the middle class in Indonesia; (2) the strategies pesantren employ to reproduce the middle class; and (3) the challenges they face in this process. The study uses a qualitative approach with a naturalistic method and a case-study design at two pesantren in Cirebon, namely Pondok Pesantren Wirausaha Kebon Cinta and Pondok Pesantren Bina Insan Mulia. Data were collected through guided open interviews, observation, and document review, then analyzed descriptively using triangulation. The findings show that the two pesantren reproduce the middle class through different yet complementary pathways: Kebon Cinta emphasizes practical entrepreneurship education (business management, marketing, and student bazaars), whereas Bina Insan Mulia emphasizes leadership, English proficiency, and further study at domestic and overseas universities. The main strategies include curriculum modernization, strengthening the pesantren economy, the use of technology, and alumni networking. The principal challenges include gaps in educational and economic access, social stigma, weak links to industry, and limited capital. The study concludes that pesantren can be effective instruments of social mobility when supported by the strengthening of students’ economic, cultural, and social capital